Analysis of “Wakamono Kotoba” in Song Lyrics on The Takayan Youtube Channel: A Sociolinguistics Study - Insan Putra, Sahid; Masrokhah, Yuni (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Wakamono kotoba is commonly used by Japanese teenagers in conversational interactions. The purpose of this study is to analyze the formation of wakamono kotoba and to describe its meaning and use in the lyrics of the Takayan song. The research method used is descriptive qualitative. The data used is in the form of song lyrics on Takayan's YouTube channel. From the data found, there are 7 formation processes used in Takayan's song lyrics for the period 2019 - 2021 which according to Yonekawa's theory contained in the data found are Shakuyou, Shouryaku, Iikae, Mojiri, Konkou, Kashirajika, and Oto No Tenka. The meaning in each wakamono kotoba has the same meaning as the words that make it up, but there are several words whose meanings refer to or indicate the expression you want to convey to others. The use of wakamono kotoba in this analysis is that there are several wakamono kotoba which have special uses or in certain places such as in message applications and also in conveying feelings or responses to others, there are also wakamono kotoba which use the same as their constituent language vocabulary or do not have special uses. The novelty of this research is in the study taken by studying sociology, as well as how the process of forming words and the meaning of these words.